Current status of food safety hazards and health risks connected with aquatic food products from Southeast Asian region - Peiru Gao; Nor Qhairul Izzreen Mohd Noor; Sharifudin Md Shaarani (Taylor & Francis, 2024)
Indexed by ERA/MYCITE